A Study on the Effect of CEO Discovery DNA on Productivity - Dae-Geun, Kim (Thammasat Review, 2020)
This study starts with the question of what is the manager’s ability to innovate and tries to confirm its effect on productivity from the point of view of discovery DNA. Research into managers’ innovation, which has been conducted in previous studies, focuses on the learning and ability development of managers, so there were many discussions from the perspective of responding to changes in the corporate environment. However, this study was approached from the viewpoint of the competency that is inherent in managers. Discovery DNA was suggested by Dyer et al. (2011) while explaining the difference between innovative entrepreneurs and ordinary entrepreneurs, and refers to five abilities: ‘questioning’, ‘observing’, ‘networking’, ‘experimenting’ and ‘associating’. The data in this study were collected from 277 companies headquartered in Korea, which were classified by size, with 62 (28%) being large companies and 149 (71%) small companies. As a result of the analysis, it was found that “questioning” and “networking” were statistically significant components of discovery DNA, which is the manager’s innovation ability, and had a positive (+) effect on productivity.